6
$\begingroup$

If $$f(x)=\frac{\sin 3x+A\sin 2x+B\sin x}{x^5},$$ $x\neq 0$, is continuous at $x=0$, then find $A,B$ and $f(0)$. Do not use series expansion or L Hospital's rule.

As $f(x)$ is continuous at $x=0$,therefore its limit at $x=0$ should equal to its value.
Note that this question is to be solved without series expansion or L Hospital's rule,

I tried to find the limit $\lim_{x\to 0}\frac{\sin 3x+A\sin 2x+B\sin x}{x^5}$
$\lim_{x\to 0}\frac{\sin 3x+A\sin 2x+B\sin x}{x^5}=\lim_{x\to 0}\frac{3\sin x-4\sin^3x+2A\sin x\cos x+B\sin x}{x^5}=\lim_{x\to 0}\frac{3-4\sin^2x+2A\cos x+B}{x^4}\times\frac{\sin x}{x}$
$=\lim_{x\to 0}\frac{3-4\sin^2x+2A\cos x+B}{x^4}$
As the denominator is zero,so numerator has to be zero,in order the limit to be finite.
So, $3+2A+B=0. (1)$

I tried but I could not get the second equation between $A$ and $B$. I am stuck here. How do I continue?

$\endgroup$
9
$\begingroup$

Using trigonometric identities we have \begin{align} 3-4\sin^2 x+2A\cos x+B&=4(1-\sin^2 x)+2A\cos\left(2\cdot\frac{x}{2}\right)+B-1\\ &=4\cos^2\left(2\cdot\frac{x}{2}\right)+2A\cos\left(2\cdot\frac{x}{2}\right)+B-1\\ &=4\left(1-2\sin^2\frac{x}{2}\right)^2+2A\left(1-2\sin^2 \frac{x}{2}\right)+B-1\\ &=16\sin^4\frac{x}{2}-16\sin^2\frac{x}{2}-4A\sin^2\frac{x}{2}+2A+B+3\\ &=16\sin^4\frac{x}{2}-4(A+4)\sin^2\frac{x}{2}+2A+B+3\\ \end{align} In order to make the limit finite we must have $$A+4=0\quad\text{and}\quad 2A+B+3=0\qquad\iff\qquad \color{blue}{A=-4}\quad\text{and}\quad \color{blue}{B=5}$$ By taking those values we get \begin{align} \lim_{x\to 0}\frac{\sin 3x\color{blue}{-4}\sin 2x+\color{blue}{5}\sin x}{x^5}&=\left(\lim_{x\to 0}\frac{16\sin^4\frac{x}{2}}{x^4}\right)\left(\lim_{x\to 0}\frac{\sin x}{x}\right)\\ &=\left(\lim_{x\to 0}\frac{\sin \frac{x}{2}}{\frac{x}{2}}\right)^4\left(1\right)\\ &=\color{blue}{1} \end{align} Since $f$ is continuous at $0$ it follows $f(0)=1$.

$\endgroup$
0
3
$\begingroup$

Your first step is correct, you need $3+2A+B=0$ for the function to converge. Let's substitute $B=-3-2A$ into the original function. Them you have

$$ f(x)=\frac{\sin(3x)+A\sin(2x)+(-3-2A)\sin(x)}{x^5} $$

Using the angle sum formulas: $$ \sin(3x)=\sin(x)\cos(2x)+\cos(x)\sin(2x)=\sin(x)(\cos^2(x)-\sin^2(x))+2\sin(x)\cos(x)^2. $$ Now, using the standard trig identity, $\sin^2(x)=1-\cos^2(x)$. Therefore, $$ \sin(3x)=4\sin(x)\cos(x)^2-\sin(x) $$

Also using the angle sum formulas: $$ \sin(2x)=2\sin(x)\cos(x) $$

Substituting these into the original function, we have $$ f(x)=\frac{4\sin(x)\cos^2(x)-\sin(x)+2A\sin(x)\cos(x)-3\sin(x)-2A\sin(x)}{x^5}. $$ By combining the terms with $A$ and those without, we have $$ f(x)=\frac{4\sin(x)(\cos^2(x)-1)+2A\sin(x)(\cos(x)-1)}{x^5}=\frac{\sin(x)}{x}\cdot\frac{4(\cos^2(x)-1)+2A(\cos(x)-1)}{x^4} $$ Factoring a difference of squares, the numerator becomes $$ f(x)=\frac{\sin(x)}{x}\cdot\frac{4(\cos(x)-1)(\cos(x)+1)+2A(\cos(x)-1)}{x^4}$$ Factoring again, we have $$f(x)=\frac{\sin(x)}{x}\cdot\frac{\cos(x)-1}{x^2}\cdot\frac{4(\cos(x)+1)+2A}{x^2} $$

Observe that $$ \lim_{x\rightarrow 0}\frac{\cos(x)-1}{x^2}=\lim_{x\rightarrow 0}\frac{\cos(x)-1}{x^2}\cdot\frac{\cos(x)+1}{\cos(x)+1}=\lim_{x\rightarrow 0}\frac{\cos^2(x)-1}{x^2(\cos(x)+1)} $$ Then, using the standard trig identities, we get that this limit equals $$ \lim_{x\rightarrow 0}\frac{-\sin^2(x)}{x^2(\cos(x)+1)}=\lim_{x\rightarrow 0}\left(\frac{\sin(x)}{x}\right)^2\frac{-1}{\cos(x)+1}, $$ which we can see has a limit of $-\frac{1}{2}$.

Continuing from here, you also need the numerator to vanish for the limit to exist because the denominator vanishes. In other words, $\lim_{x\rightarrow 0}4(\cos(x)+1)+2A=8+2A$ must be $0$, so $A=-4$. After substitution, the entire formula becomes $$f(x)=\frac{\sin(x)}{x}\cdot\frac{\cos(x)-1}{x^2}\cdot\frac{4(\cos(x)-1)}{x^2} $$ Substituting the values that we've calculated the limit as $$ \lim_{x\rightarrow 0}f(x)=1\cdot\left(-\frac{1}{2}\right)\cdot\left(-\frac{4}{2}\right)=1. $$

$\endgroup$
6
  • 1
    $\begingroup$ You made a typographical error. After you write "factoring a difference of squares, the numerator becomes," you have a product of two quotients. The denominator of the second quotient should be $x^{4}$. $\endgroup$ – user74973 Dec 19 '15 at 15:21
  • $\begingroup$ @user74973 Thanks and corrected. $\endgroup$ – Michael Burr Dec 19 '15 at 16:14
  • $\begingroup$ I spied one other typographical error. In your expansion of sin(3x), you have "$\sin(x)^{2}$" instead of "$\sin^{2}x$." May I suggest that you use an algin environment in your equivalent expression for $f(x)$ after you write "by combining the terms with $A$ and those without, we have ..."? You "should" have the quotient $\sin{x}/x$ on the next line. (By the way, you may want to consider writing "$\sin{x}$" instead of "$\sin(x)$" and writing "$\cos{x}$" instead of "$\cos(x)$.") $\endgroup$ – user74973 Dec 19 '15 at 20:03
  • $\begingroup$ I should say that you have a nice argument. May I make a suggestion to make it more lucid? If you suppose the reader knows how to factor a difference of two squares and the value of the limit of $(1 - \cos{x})/x^{2}$ at 0, you can write consecutively seven equivalent expressions for $f(x)$ in a single align environment, and with the last expression, you can evaluate the limit of the function at 0. $\endgroup$ – user74973 Dec 19 '15 at 20:03
  • $\begingroup$ @user74973 Thanks for the suggestions. I'm on my phone right now, so I won't attempt the changes right away. $\endgroup$ – Michael Burr Dec 19 '15 at 20:24
1
$\begingroup$

\begin{align*} f(x) &= \frac{\sin(3x) + A\sin(2x) + B\sin{x}}{x^{5}} \\ &= \frac{(-4\sin^{3}x + 3\sin{x}) + 2A\sin{x}\cos{x} + B\sin{x}}{x^{5}} \\ &= \frac{\sin{x}}{x} \cdot \frac{-4\sin^{2}x + 3 + 2A\cos{x} + B}{x^{4}} \\ &= \frac{\sin{x}}{x} \cdot \frac{-4\sin^{2}x + 3 + 2A\cos{x} + B}{x^{4}} \\ &= \frac{\sin{x}}{x} \cdot \frac{4(1 - \sin^{2}x) - 1 + 2A\cos{x} + B}{x^{4}} \\ &= \frac{\sin{x}}{x} \cdot \frac{-4(1 - \cos^{2}x) + 3 + 2A\cos{x} + B}{x^{4}} . \end{align*} The given function is defined at $0$ if, and only if, $3 + 2A + B = 0$. So, $B = -3 - 2A$, and \begin{align*} f(x) &= \frac{\sin{x}}{x} \cdot \frac{-4(1 - \cos^{2}x) - 2A(1 - \cos{x})}{x^{4}} \\ &= \frac{\sin{x}}{x} \cdot \frac{1 - \cos{x}}{x^{2}} \cdot \frac{-4 - 2A - 4\cos{x}}{x^{2}} . \end{align*} Again, the given function is defined at $0$ if, and only if, $-4 - 2A -4 = 0$. So, $A = -4$, $B = 5$, and \begin{align*} f(x) &= \frac{\sin{x}}{x} \cdot \frac{1 - \cos{x}}{x^{2}} \cdot \frac{4(1 - \cos{x})}{x^{2}} \\ &= 4 \cdot \frac{\sin{x}}{x} \cdot \frac{1 - \cos{x}}{x^{2}} \cdot \frac{1 - \cos{x}}{x^{2}} . \end{align*} So, $\lim_{\scriptscriptstyle{x\to0}} f(x) = 1$.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.